Téte-à-téte avec Hamlet ou Jules Laforgue et George Rodenbach suites sur les pas de William Shakespeare - Lewandowska, Alicja (Wydawnictwo Naukowe UAM, 2008)
The aim of the paper at hand is to find parallel elements between the following two texts: Jules Laforgue's Hamlet, ou les suites de la piété filiale (1886) and George Rodenbach's Bruges-la-Morte (1892), in relation to William Shakespeare's play. Our analysis is of a three-level character. Firstly, it is concerned with a comparison of biographies of the two 19th century authors. Secondly, it takes into its scope the plot events of both texts in question. Thirdly, it attempts to explain the linguistic transposition of poetry into prose. The final goal of this perusal is a demarcation of common points of reference between the three texts, which, in turn, is to prove Hamlet's intertextuality.
Rendez-vous with Hamlet or Jules Laforgue and George Rodenbach in the footseps of William Shakespeare
Keywords: Laforgue Jules; Rodenbach George; Shakespeare William